Protein transport and processing by human HT29-19A intestinal cells: effect of interferon γ. Issue 4 (1st April 1998) - Terpend, K; Boisgerault, F; Blaton, M A; Desjeux, J F; Heyman, M
Abstract : Background —The nature of the breakdown products produced in enterocytes during epithelial transport of intact proteins may be critical in determining the functional consequences of protein absorption. Aim —( a ) To measure the transepithelial transport of horseradish peroxidase (HRP) and to identify the nature of HRP breakdown products released on the basal side of enterocytes and ( b ) to assess the role of interferon γ (IFNγ) on HRP transport and processing. Methods —HT29-19A intestinal cells were used to assess transepithelial transport of HRP in Ussing chambers, and the nature of breakdown products in the basal compartment was analysed by high performance liquid chromatography (HPLC). Results —(1) In control conditions, [ 3 H]HRP equivalent fluxes (3135 (219) ng/h per cm 2 ; mean (SEM)) comprised 50% amino acids, 40% peptides, and 10% intact HRP. Steric exclusion HPLC of the breakdown products indicated a wide range of molecular masses including a major peptide of about 1150 Da. Lysosomal aspartyl and thiol proteases were expressed but no HLA-DR surface expression was noted. (2) At 48 to 72 hours after IFNγ stimulation, [ 3 H]HRP equivalent fluxes increased significantly (7392 (1433) ng/h per cm 2 ) without modification of the relative proportions of amino acids, peptides, and intact HRP, and without modification of the distribution of breakdown products in HPLC. Lysosomal protease activities were not modified by IFNγ but HLA-DR expression was increased. Conclusion —Intestinal cells are able to process HRP into peptides potentially capable of stimulating the immune system. IFNγ stimulates the transport and processing of HRP thus increasing the antigenic load in the intestinal mucosa.